Exploring the Role of Environmental Knowledge, Awareness, and Organizational Behavior in Driving Sustainability Performance and Decision-Making: Evidence from Somali Business Organizations - Ali, Ali Yassin Sheikh; Nor, Abukar Hussein (International Review of Management and Marketing, 2025)
This study investigates the influence of environmental knowledge, awareness, and organizational behavior on sustainability performance and decision-making in Somali organizations. This study reveals that, although environmental knowledge has historically been deemed essential for fostering sustainability, it is inadequate on its own to produce tangible sustainability results. Environmental knowledge serves as a crucial predictor of sustainability success, both directly and via the mediation influence of organizational behavior. The research used a quantitative approach, employing a standardized questionnaire administered to 300 employees from several firms in Somalia. Data analysis, encompassing Exploratory Factor Analysis (EFA), correlation, mediation testing, and ANOVA, was performed utilizing Jamovi 2.6.2 and SPSS 27 to evaluate the interrelations among the research variables. The findings demonstrate that organizational behavior acts as a vital conduit for converting environmental information into sustainable behaviors, underscoring the significance of leadership, culture, and policy support in sustainability efforts. Moreover, demographic variables like age, job experience, and education substantially affect environmental knowledge, awareness, and participation in sustainability, with older, more experienced, and better educated persons demonstrating more robust sustainability-related behaviors. Conversely, environmental awareness, although favorably associated with sustainability performance, does not have a statistically meaningful direct impact. These findings highlight the necessity for firms to progress beyond mere awareness campaigns and engage in systematic sustainability education programs, leadership-driven policies, and working cultures that promote sustainable practices. Through the integration of knowledge-based interventions, organizational participation, and systematic decision-making processes, organizations in Somalia can attain enduring enhancements in sustainable performance. The study offers significant insights for policymakers, corporate leaders, and academics aiming to improve sustainability practices using evidence-based initiatives that emphasize environmental knowledge and efficient organizational behavior frameworks.